Architectures of an “Otherwise”: Inhabiting Displacement - Somayeh Chitchian; Maja Momic; HafenCity University Hamburg; Department of Urban Design – maja [dot] momic [at] hcu-hamburg [dot] de; Shahd Seethaler-Wari (Ardeth, 2020)
This concept paper aims to destabilize the limits and delineations of conventional architectural thinking by disclosing its ambiguities and contingencies through the centralization of the inhabitation-displacement nexus and, by extension, the figure of the inhabitant. Building upon our January 2019 workshop at the Max Planck Institute for the Study of Religious and Ethnic Diversity in Germany, entitled: Inside Out – Outside In: Shifting Architectures of Refugee Inhabitation, its keynote interventions by Prof. Anooradha Iyer Siddiqi and Prof. Romola Sanyal, together with the vast array of topics and methodologies brought to the table by our presenters, we primarily argue towards the concept of inhabitation as an epistemic shift of both the site and the subject of architectural (knowledge) production. Shifting our focus particularly to the sites and subjects of displacement (i.e., ‘the refugee’/ ‘the migrant’ and beyond) enabled us to centralize the concept of inhabitation as a modality of the architectural spatial production of an otherwise through the prime subject figure of architectural authorship: the inhabitant.